Synthesis and evaluation of Niobium or Vanadium – doped heteropolyacid catalysts in oxidation and acetalization reactions of alcohols and aldehydes derivated of biomass - Vergara Torres, John Alexander (2022)
Aldehydes derived from biomass and terpene alcohols are abundant raw materials, of plant origin, and of interest for production of fine chemicals products, such as fragrances, pharmaceuticals and agrochemicals. Recently, for economic and environmental reasons, catalytic processes have been developed to transform these renewable resources into chemical products with higher added value. In this work, heteropolyacids (HAPs) obtained from phosphomolybdic acid doped with 1, 2, and 3 mol of Niobium (i.e., H 4 PMo 11 Nb 1 O 40 , H 5 PMo 10 Nb 2 O 40 and H 6 PMo 9 Nb 3 O 40 ) were synthesized and evaluated as catalysts in oxidation and acetalization reactions of aldehydes present in the biomass. Niobium- doped HAPs were synthesized from different precursors: MoO 3 , Nb 2 O 5 , H 3 PO 4. Furthermore, HAPs obtained from the doping of phosphomolybdic acid with Vanadium were applied in oxidation reactions of terpene alcohols by hydrogen peroxide in acetonitrile solutions. The synthesis procedures used proved to be efficient, since the catalyst were obtained with satisfactory yields. All synthesized acids were characterized by infrared spectroscopy analysis, ultraviolet-visible spectroscopy, thermal analysis, surface area and porosimetry, X-ray diffraction, and potentiometric titration. The catalytic activity of HAPs was evaluated in different oxidation and acetalization reactions. The Nb-doped HAPs were evaluated in oxidative esterification reaction of furfural, chosen as a model substrate due to its reactivity and industrial interest. In addition, they were also evaluated in acetalization reaction. In this reaction, the amount of Nb does not seem to have produced a significant difference in terms of conversion and selectivity. Furthermore, most of the catalytic tests were performed with H 6 PMo 9 Nb 3 O 40 obtaining conversion of approximately 50% and 2-furfuraldehyde-methylacetal as the only product. The concentration of 0.0312 mol % of catalyst presents the best catalytic activity. Finally, the reaction was extended to benzaldehyde, obtaining similar results. Tests performed with Vanadium-doped catalysts showed that H 4 PMo 11 VO 40 was the most active and selective in the oxidation of geraniol (the substrate chosen as model terpene alcohol) toward geraldehyde, mono and diepoxide, with epoxide being the major product. Conversion greater than 94% was obtained with selectivity between 80 and 85% for epoxide geraniol. H 4 PMo 11 VO 40 has also been tested in the oxidation of other terpene alcohols, and has been shown to be active in the oxidation of nerol. Keywords: Furfural. Terpene alcohols. Keggin Heteropolyacids. Oxidative esterification